What, if any, are our obligations to alleviate poverty? - Child, Richard Grenville (My University, 2015)
Before the Industrial Revolution, almost everyone, excluding the ruling class, was poor. Today approximately 43% of the world’s population lives on less than $2 per day, i.e. in poverty. The standard view is that because poverty negatively affects the poor’s ability to lead a ‘normal’ flourishing life, the wealthy, therefore, have an obligation to alleviate this poverty. I reject this view. Analysis of the nature of poverty reveals that only the poor themselves can truly overcome their poverty by changing their economic belief systems. It is these systems which keep them poor. Repeating the same historically ineffective economic actions does not lead to changed outcomes. Prescriptions, aid and charity have not helped. Viewing the poor as fully-capable, autonomous human beings (Kantian ends-in-themselves), I argue that our obligations are not grounded on human rights, equality, fairness or justice. Rather our moral obligations are to support the appropriate plans of the poor.